P0695ANALYSIS OF HOSPITALIZATION EVENTS IN NON-DIALYSIS CKD PATIENTS. (6th June 2020) - Mandreoli, Marcora; Gibertoni, Dino; Santoro, Antonio
Abstract: Background and Aims: Data are limited about rates and causes of hospitalization in patients with Chronic Kidney Disease (CKD) during maintenance period. In the present study, we investigate the amount, characteristics and trends of hospital admissions in a large cohort of pre-dialysis CKD patients followed within the Emilia-Romagna Region (Italy) PIRP project. Method: Patients who were enrolled in the PIRP project in the period 1.4.2004-31.12.2018 constitute the study population. The PIRP database contains clinical and laboratory data collected at each follow-up visit. Hospitalization data regarding admissions occurred during patients' follow-up in PIRP were obtained from the regional hospital discharges database through unique individual linkage. Day-hospital admissions and hospitalizations aimed at arteriovenous fistula creation and peritoneal catheter placement were excluded. Results: In almost 15 years of observation, 27, 886 patients were enrolled in PIRP, mostly males (65, 3%) with baseline median age of 75 years and baseline median eGFR=32.3 mL/min/1.73m2. Among them, 19, 288 (69.2%) generated 72, 432 hospitalizations during their follow-up in the project. The number of hospitalizations per person/year was 1.06 overall, increasing from 0.38 for stage CKD 1 to 1.93 for stage CKD 5 (Fig.1). The median length of stay was 9 days. Overall, cardio-vascular diseases were the main cause of hospitalization (30.0% of admissions), with renal diseases, tumors and respiratory diseases each accounting for over 10% of admissions, although the distribution of causes of hospitalization varies according to CKD stage (Fig.2). About one fifth of patients had one or more hospitalizations for acute kidney injury. The trend analysis revealed a steadily decreasing hospitalization rate for patients that were on CKD stage 4 and 5 at baseline, a constant hospitalization trend over time for patients who began their follow-up in stages 1 to 3a, while hospitalization rate of patients in CKD 3b stage declined after 9 years (Fig 3). Conclusion: The study broadens our knowledge on the hospitalizations "consumption" by the population with CKD in the non-dialysis phase. It confirms that patients with CKD represent a vulnerable population, needing about 1 hospitalization / year / patient. The trend towards a reduction in hospitalizations during the follow-up period could be traced back to the specific care model, which encourages a more frequent management of patients in the Nephrology clinics.